Reprocessable Non-Isocyanate Polyurethane Vitrimers - Anna Chrobok; Damian Kiełkiewicz; Agnieszka Siewniak (Open Journal of Chemistry - Peertechz Publications, 2023)
Non-isocyanate polyurethanes (NIPUs, polyhydroxyurethanes, PHUs), have emerged as sustainable alternatives to conventional isocyanate-polyol polyurethanes. However, the permanent cross-links in traditional linear, crosslinked polyhydroxyurethane polymer networks hinder their recyclability for high-value applications. In this study, we provide a comprehensive overview of polyhydroxyurethane vitrimers - polymers with intrinsic recyclability - containing dynamic covalent adaptable bonds that allow them to be reprocessed or self-healed under external stimuli such as heat or solvents. These materials exhibit a unique combination of the attributes of thermosets, such as improved heat stability, solvent resistance or enhanced mechanical properties, and the reprocessability of thermoplastics. Various strategies have been explored to enable the reprocessability of PHUs. External catalysts, such as 4-(dimethylamino)pyridine (DMAP) have been used to facilitate exchange reactions and promote reprocessing. Additionally, the use of functionalized silica nanoparticles as reinforcing fillers has influenced the material's behavior during reprocessing. Another method involved the incorporation of dynamic disulfide bonds to expedite reprocessing times for PHU networks, while dissociative dynamic chemistry has enabled self-healing behavior in certain partially cross-linked NIPUs. These advancements demonstrate the potential for tailoring the reprocessability and mechanical attributes of NIPUs, paving the way for sustainable and versatile polymeric materials, and addressing the environmental concerns associated with traditional polyurethanes.